Possible Amelioration of the Severity of Nutritional Steatohepatitis by Guggulsterone in Mice: guggulsterone and steatohepatitis in mice - Nafeer, Sara Ameen; Zalzala, Munaf (Iraqi Journal of Pharmaceutical Sciences, 2019)
Non-alcoholic fatty liver disease (NAFLD) has become one of the most common chronic liver diseases worldwide, which characterized by steatosis, inflammation, and fibrosis. The aim of this designed study is to evaluate the ability of guggulsterone to prevent high fat diet induced steatohepatitis in mice. Five groups of male mice were selected and treated as the following: group I, mice had free access to standard commercial diet and considered as control group, group II, mice were fed a specially formulated high-fat diet for 12 weeks to induce non-alcoholic liver disease, while groups III, IV and V the mice were administered high fat diet containing guggulsterone at 500, 1000 and 2000 ppm concentration respectively for 12 weeks. Maintaining mice on fat rich diet only resulted in inducing the metabolic and histological NAFLD associated. While the treatment with guggulsterone significantly improves the evaluated markers. These results demonstrate guggulsterone may be useful in preventing the development of steatohepatitis.